From sick old man to mythical hero - Sandra Pitcher; Tammy Frankland; Nicola Jones (Communicare)
In his autobiography, Conversations with Myself, Mandela spoke about his concern that the world had a false image of him as a saint and semi-god (Mandela, 2012). However, it can be noted that Mandela and the ANC carefully built up his symbolic power in the press and media to represent him as “some kind of Messiah” (Ottaway, 1993:11) who had led South Africa to freedom almost single-handedly, and in doing so cemented his ideals of liberation, peace and non-racialisation in the imagination of the world. However, as Mandela’s health deteriorated before his death, his constructed immortality was tested as society began to question if his legacy could live on without the physical presence of ‘Mandela the man’. Consequently, this article examines the representation of Mandela in his few final years. In an examination of the Independent Online news repository in 2010 and 2013, this research highlights how ‘Madiba’s Magic’ was a carefully constructed media image and one that, during his long illness, forced South Africans, and the world, to recognise his ‘humanness’. The paper concludes, however, by documenting the immense power of Mandela’s legacy as played out in the press, and how, after death, his carefully constructed legacy rose above the damage of his prolonged illness, elevating him from a sick old man and reinforcing him as a mythical revolutionary.